Perioperative FOLFOX 4 Versus FOLFOX 4 Plus Cetuximab Versus Immediate Surgery for High-Risk Stage II and III Colon Cancers: A Phase II Multicenter Randomized Controlled Trial (PRODIGE 22). Issue 4 (April 2020) - Karoui, M.; Rullier, A.; Piessen, G.; Legoux, J. L.; Barbier, E.; De Chaisemartin, C.; Lecaille, C.; Bouche, O.; Ammarguellat, H.; Brunetti, F.; Prudhomme, M.; Regimbeau, J. M.; et al.
Abstract : Background: Perioperative chemotherapy has proven valuable in several tumors, but not in colon cancer (CC). Objective: The aim of this study was to evaluate the efficacy and safety of perioperative chemotherapy in patients with locally advanced nonmetastatic CC. Methods: This is a French multicenter randomized phase II trial in patients with resectable high-risk T3, T4, and/or N2 CC on baseline computed tomography (CT) scan. Patients were randomized to receive either 6 months of adjuvant FOLFOX after colectomy (control) or perioperative FOLFOX for 4 cycles before surgery and 8 cycles after (FOLFOX peri-op). In RAS wild-type patients, a third arm testing perioperative FOLFOX-cetuximab was added. Tumor Regression Grade (TRG1) of Ryan et al was the primary endpoint. Secondary endpoints were toxicity, perioperative morbidity, and quality of surgery. Results: A total of 120 patients were enrolled. At interim analysis, the FOLFOX-cetuximab arm was stopped (lack of efficacy). The remaining 104 patients (control, n = 52; FOLFOX preop n = 52) represented our intention-to-treat population. In the FOLFOX perioperative group, 96% received the scheduled 4 cycles before surgery. R0 resection and complete mesocolic excision rate were 94% and 93%, respectively. Overall mortality and morbidity rates were similar in both groups. Perioperative FOLFOX chemotherapy did not improve major pathological response rate (TRG1 = 8%) but was associated with a significant pathological regression (TRG1-2 = 44% vs 8%, P < 0.001) and a trend to tumor downstaging as compared to the control group. CT scan criteria were associated with a 33% rate of overstaging in control group. Conclusions: Perioperative FOLFOX for locally advanced resectable CC is feasible with an acceptable tolerability but is not associated with an increased major pathological response rate as expected. However, perioperative FOLFOX induces pathological regression and downstaging. Better preoperative staging tools are needed to decrease the risk of overtreating patients Abstract : Supplemental Digital Content is available in the text